KAJIAN KONSEP PERANCANGAN TAMAN SEHAT PADA LAYOUT TAMAN HOTEL BUTIK DI KAWASAN EKOWISATA - Aprilia Tanuy, Rieka; Wilianto, Herman (Jurnal Riset Arsitektur, 2022)
Abstract - A healthy lifestyle has become rife in recent years. The pressures of urban life make more people aware and start to care about health and well-being. A regular diet, balanced nutritional intake, and various types of sports become a new lifestyles. People are starting to look for a place to take a temporary break, one of which is eco-tourism. Returning to nature is believed to be able to restore the energy used. The widespread need for open space that supports a healthy lifestyle in the community has encouraged various business actors to fulfill it. Gardens at the hotel no longer function as a mere green area. Several hotels that have developed a design concept based on a healthy lifestyle have begun to arrange their gardens. However, the arrangement of the gardens at these hotels is generally still not sufficient to serve as a support for a healthy lifestyle for visitors. Therefore, this study examines the concept of a healthy garden in a boutique hotel landscape based on healthy lifestyle. This qualitative research uses an exploratory descriptive method on the two selected precedents, namely Klub Bunga Boutique Resort and Park Royal on Pickering based on related issues. The conclusion of this study is a general guideline for designing healthy gardens in boutique hotels, although it is still necessary to take into account the local context. Keywords: healthy lifestyle, healthy garden, boutique hotel